Efficacy of Individual Bacteriophages Does Not Predict Efficacy of Bacteriophage Cocktails for Control of Escherichia coli O157 - Niu, Yan D.; Liu, Hui; Du, Hechao; Meng, Ruiqiang; Sayed Mahmoud, El; Wang, Guihua; McAllister, Tim A.; Stanford, Kim (Frontiers in Microbiology, 2021)
Effectiveness of bacteriophages AKFV33 (Tequintavirus, T5) and AHP24 (Rogunavirus, T1), wV7 (Tequatrovirus, T4), and AHP24S (Vequintavirus, rV5), as well as 11 cocktails of combinations of the four phages, were evaluated in vitro for biocontrol of six common phage types of Escherichia coli O157 (human and bovine origins) at different multiplicities of infection (MOIs; 0.01–1,000), temperatures (37 or 22°C), and exposure times (10–22 h). Phage efficacy against O157 was highest at MOI 1,000 (P < 0.001) and after 14-18 h of exposure at 22°C (P < 0.001). The activity of individual phages against O157 did not predict the activity of a cocktail of these phages even at the same temperature and MOI. Combinations of phages were neutral (no better or worse than the most effective constituent phages acting alone), displayed facilitation (greater efficacy than the most effective constituent phages acting alone), or antagonistic (lower efficacy than the most effective constituent phages acting alone). Across MOIs, temperatures, exposure time, and O157 strains, a cocktail of T1, T4, and rV5 was most effective (P < 0.05) against O157, although T1 and rV5 were less effective (P < 0.001) than other individual phages. T5 was the most effective individual phages (P < 0.05), but was antagonistic to other phages, particularly rV5 and T4 + rV5. Interactions among phages were influenced by phage genera and phage combination, O157 strains, MOIs, incubation temperatures, and times. Based on this study, future development of phage cocktails should, as a minimum, include confirmation of a lack of antagonism among constituent phages and preferably confirmation of facilitation or synergistic effects.